1977
DOI: 10.1159/000152856
|View full text |Cite
|
Sign up to set email alerts
|

A Mapping Function for Man

Abstract: Assuming a perfect correspondence between the site of crossing-over and an observed chiasma, data on meiosis in the human male are used to estimate a mapping parameter which on average turns out to be intermediate between the Kosambi and Carter-Falconer values, but smaller for acrocentrics. A table is given for converting recombination frequencies to map distances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
4

Year Published

1985
1985
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 7 publications
1
43
1
4
Order By: Relevance
“…For small chromosomes, the parameter estimates for the p arms tend to be higher than those for the q arms, but they have a great deal more variability, thus the two interval estimates overlap for all the chromosomes where estimates for both arms are available. However, we caution that this should not be viewed as contradictory to the results in Forabosco et al (1995), whose data suggested different levels of interference between the p arm and the q arm of chromosome 1 using Rao's map function (Rao et al 1977). There are several possible explanations for the discrepancy between the results from our analysis and theirs.…”
Section: contrasting
confidence: 92%
“…For small chromosomes, the parameter estimates for the p arms tend to be higher than those for the q arms, but they have a great deal more variability, thus the two interval estimates overlap for all the chromosomes where estimates for both arms are available. However, we caution that this should not be viewed as contradictory to the results in Forabosco et al (1995), whose data suggested different levels of interference between the p arm and the q arm of chromosome 1 using Rao's map function (Rao et al 1977). There are several possible explanations for the discrepancy between the results from our analysis and theirs.…”
Section: contrasting
confidence: 92%
“…In the genetic map we estimated the interference parameter p in the Rao (1977) mapping function at 0.28 and typing error frequency E at 0.004 (Shields et al 1991) for the sequence order constrained map. The sex-averaged map length ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Computer programs in common use for constructing linkage maps assume no chiasma interference for the computation of multilocus likelihoods and may then convert the resulting map to approximate conformity with the Kosambi function, which is not multipoint feasible. Studies of chiasma interference in humans have shown that it exists at greater levels than the Kosambi function provides and appears to vary among chromosomes (19)(20)(21). The estimate of t is significantly lower for smaller autosomes (Fig.…”
Section: Unexpected Variation In Estimates Of Effective Bottleneck Timementioning
confidence: 99%